Xiao Qing Long Tang ameliorates neutrophil extracellular trap-dendritic cells-T helper 17 cell axis in Neutrophilic Asthma - Xiaoying Ji; Hongda Chen; Sheng-dong He; Min Huang; Xiaoli You; Chuan Xiao; Zhifeng Chen; Jinwen Cai (PLoS ONE, 2025)
Background Neutrophilic asthma (NA) is an allergic airway inflammation disease featuring heterogeneous neutrophil infiltration, which is driven by the interactions between dendritic cells (DCs) and T helper (Th) 17 cells. Neutrophils release neutrophil extracellular traps (Nets), which promote disease progression and glucocorticoid resistance. Therefore, targeting the interaction among Nets, DC and Th17 is a promising pathway for preventing organ damage. Traditional Chinese Medicine (TCM), especially Xiao-qing-long-tang (XQLT), has shown potential in managing eosinophilic asthma by modulating Th2 cell-mediated inflammation, reducing eosinophilic infiltration, and airway remodeling. However, XQLT’s effect on Nets and DCs-Th17 interactions in NA remains unclear. Methods We developed two models: an ovalbumin (OVA)/lipopolysaccharide (LPS)-induced NA mouse model with interventions using either XQLT or sivelestat, and a series of bone marrow-derived dendritic cells (BMDCs)-Th17 cell differentiation models induced by Nets, OVA/LPS, OVA/LPS/Nets, XQLT, OVA/LPS/Nets/XQLT, or corresponding inhibitors. The chemical composition of XQLT was analyzed using ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). Key parameters were evaluated via histopathology, immunohistochemistry, immunofluorescence scanning, flow cytometry, Western blot (WB) analysis, and enzyme-linked immunosorbent assay (ELISA). Results In OVA/LPS-induced mice, treatment with sivelestat in OVA/LPS-induced mice reduced airway inflammation, Nets formation characterized by citrullinated histone H3 (CitH3) and myeloperoxidase (MPO) expressions, Th2/17 cell proportions in lungs, and interleukin (IL)-4, 6, 17, and 23 levels in bronchoalveolar lavage fluid (BALF). In vitro, OVA/LPS/Nets promoted IL-6/23 secretions and Th17 differentiation through increased p38 mitogen-activated protein kinase (MAPK)/nuclear factor κB (NF-κB) signaling phosphorylation in DCs. Fifty-one compounds were identified in XQLT, with 11 predicted to bind MAPK proteins with high affinity. XQLT significantly inhibited Nets-DCs-Th17 Axis and p38MAPK/NF-κB signaling in both NA mouse and cell models. Conclusion XQLT offered a promising treatment strategy for regulating the Nets-DCs-Th17 axis in NA.